SİLAH RUHSATI ALMAK İÇİN HASTANEYE BAŞVURANLARDA DÜRTÜSELLİK, AGRESYON, ALEKSİTİMİ VE KİŞİLİK ÖZELLİKLERİNİN DEĞERLENDİRİLMESİ - BABÜR, SABRİYE YEŞİM (Fırat Üniveristesi, 2022)
Günümüzde bireysel silahlanma artışı hem toplumumuz hem de dünya genelinde büyük bir sorun teşkil etmektedir. Silahlanmadaki artış ve evde silah bulundurma intiharları, kazaları ve aile içi şiddet oranlarını arttırmaktadır. Türkiye'de toplumun genel olarak ateşli silahlara karşı eğilimi olduğu bilinmektedir. Türkiye'de silah bulundurma ya da taşıma talebi olan her bireyin silah ruhsatı alması gerekir. Kişilik, bireyin bilişsel ve duygusal değerlendirmelerine dayanarak iç ve dış dünyaya uyum için geliştirmiş olduğu duyuş, düşünüş ve davranış örüntülerinden meydana gelir. Kişilik bozukluğu kişinin içinde yaşadığı kültürün beklentilerinden belirgin olarak sapan, süreklilik gösteren, bilişsel, duygulanım ve davranış örüntüsü olarak tanımlanmaktadır. Kişilik bozuklukları ilk olarak DSM-III'te ayrı bir eksende yer almıştır. Sunduğumuz tez çalışmasında 132 vaka ve 69 sağlıklı kontrol karşılaştırıldı. Vaka grubumuz silah ruhsatı almak, silahlı özel güvenlik ve koruculuk yapmak için başvuranlardan oluşmaktadır. Tüm katılımcılar sosyodemografik ve klinik özellikleri açısıdan değerlendirildi. Her iki grup karşılaştırıldığında Barratt toplam puanı, bilişsel düzensizlik, sabırsızlık, oto-kontrol, dikkatsel dürtüsellik ve plansız dürtüsellik alt ölçek puanları bakımından anlamlı farklılıklar bulundu. Buss Perry ölçek puanları karşılaştırıldığında kontrol grubunun öfke puanı vaka grubundan anlamlı düzeyde yüksek bulundu. MMPI profilleri değerlendirildiğinde erkeklik-kadınlık indeksi kontrol grubunda vaka grubuna göre istatistiksel olarak anlamlı derecede daha yüksekti. Aleksitimi ölçeği puanlarında iki grup arasında anlamlı farklılık bulunmadı. Katılımcı sayısının az olması, vaka ve kontrol grubunun sayısının eşit olmaması, erkek kadın oranlarının eşit olmaması çalışmamızın kısıtlılıklarıdır. Katılımcı sayısının daha fazla olduğu çalışmalarla sunduğumuz verilerin daha iyi ortaya konacağı kanaatindeyiz. Anahtar Kelimeler: Silah ruhsatı, Kişilik Bozuklukları, Şiddet, Özel güvenlik

Evaluation of Impulsivity, Aggression, Alexithymia, and Personality Traits in Persons Applying to Hospitals to Obtain Weapon License Nowadays, the increase in individual armament poses a great problem both in our society and in the world. The increase in armament and the possession of a gun at home increase the rates of suicides, accidents and domestic violence. It is known that the society in Turkey generally has a tendency towards firearms. Every individual who wishes to possess or carry a gun in Turkey must obtain a gun license. Personality consists of the patterns of affect, thinking and behavior that the individual has developed to adapt to the inner and outer world based on the person cognitive and emotional evaluations. Personality disorder is defined as a continuous cognitive, affective and behavioral pattern that deviates significantly from the expectations of the culture in which the person lives. Personality disorders were first included in a separate axis in DSM-III. In our thesis study, 132 cases and 69 healthy controls were compared. Our case group consists of applicants for obtaining a gun license, armed private security guards and village guards. All participants were evaluated in terms of sociodemographic and clinical characteristics. When both groups were compared, significant differences were found in terms of Barratt total score, cognitive dysregulation, impatience, auto-control, attentional impulsivity and unplanned impulsivity subscale scores. When Buss Perry scale scores were compared, the anger score of the control group was found to be significantly higher than the case group. When the MMPI profiles were evaluated, the male-female index was statistically significantly higher in the control group than in the case group. There was no significant difference between the two groups in alexithymia scale scores. The limited number of participants, the unequal number of case and control groups, the unequal male-female ratios are the limitations of our study. We believe that the data we presented will be presented better with studies in which the number of participants is higher. Keywords: Gun license, Personality Disorders, Violence, Private security
Evaluation of impulsivity, aggression, alexithymia, and personality traits in persons applying to hospitals to obtain weapon license
Keywords: Psikiyatri